Ambivalent Appropriation: Engagement with Apollo in Jewish and Christian Texts and Material Culture - Stewart Lester, Olivia (Journal of early Christian history, 2020)
This article considers ancient Jewish and Christian engagement with Apollo traditions in texts and material objects from the second century BCE to the sixth century CE. I track a shared strategy in which both Jews and Christians adopt imagery or tropes that surround Apollo, but either (1) reassign them to their god or Jesus, or (2) relocate them within spaces devoted to the worship of their god. In light of Roman imperial use of Apollo traditions, I draw on postcolonial theory to suggest that we might label this recurrent transformative strategy “ambivalent appropriation.” Persistent ambivalent appropriation of Apollo traditions by ancient Jews and Christians counters ancient narratives about Apollo’s prophecy at Delphi declining and/or ceasing, thereby challenging any notion of a twilight for Delphic prophecy.